De La Mettrie's Ghost The Story Of Decisions - Nunn, C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2005)
This book is about how we make choices. Drawing together evidence from 21st century chemistry to Victorian politics, enlightenment philosophy, Roman drama and beyond, it is a compelling hunt for the nature of free will.
Accessibility summary: This PDF is not accessible. It is based on scanned pages and does not support features such as screen reader compatibility or described non-text content (images, graphs etc). However, it likely supports searchable and selectable text based on OCR (Optical Character Recognition). Users with accessibility needs may not be able to use this content effectively. Please contact us at accessibilitysupport@springernature.com if you require assistance or an alternative format.
Inaccessible, or known limited accessibility
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Philosophy of mind; Science -- History; Science -- Philosophy; Psychology; Social sciences -- History; Social sciences; Humanities; Engineering; Philosophy of Mind; History of Science; Philosophy of Science; History of Psychology; Humanities and Social Sciences; Technology and Engineering